2012
DOI: 10.1111/j.1346-8138.2012.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Helicobacter pylori in common rosacea subtypes: A genotypic comparative study of Egyptian patients

Abstract: Helicobacter pylori was incriminated as an etiological factor of rosacea. However, there is still controversy about this association. We conducted a comparative study in order to assess the role of H. pylori in rosacea patients who had dyspeptic symptoms. The study included 68 patients and 54 controls. Screening for H. pylori was performed and positive cases were referred for gastric endoscopy. The inflammatory response and bacterial density were evaluated in gastric biopsy. H. pylori vacA alleles, cagA and ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
1
24
1
2
Order By: Relevance
“…Many reports have been published on the prevalence of H. pylori infection among patients with rosacea (11,(18)(19)(20)(21)(22)(23), which ranges from studies reporting prevalence of 100% to studies indicating no significant difference between healthy people and the rosacea group (24, 25). Despite intense investigations on the spread of rosacea, the precise etiology remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have been published on the prevalence of H. pylori infection among patients with rosacea (11,(18)(19)(20)(21)(22)(23), which ranges from studies reporting prevalence of 100% to studies indicating no significant difference between healthy people and the rosacea group (24, 25). Despite intense investigations on the spread of rosacea, the precise etiology remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors suggest a causal relationship between the two disorders, based on the RS clinical improvement after HP treatment (2,3,4,5) and the high incidence of this microorganism in RS patients (6,7). Improvment in the symptomatology of the disease noticed after the treatment of HP infection is supported by several studies, while other authors consider that this treatment and RS evolution are not connected (8,9).…”
Section: Results Resultsmentioning
confidence: 67%
“…In their study, 67% of the patients with RS with dyspeptic symptoms had anti-CagA (cytotoxin associated gene A) antibodies compared to 32% of the patients without RS but complaining of dyspepsia (11). At a later date Argenziano et al confirmed a predominance of anti-Cag A antibodies in RS patients (10) and El-Khalawany M et al recently proved that this virulent strain of HP is more frequently positive in papulo-pustular cases and its presence is responsible for an ampler inflammatory response in both gastric mucosa and cutaneous lesions (7).…”
Section: Results Resultsmentioning
confidence: 99%
“…Before the test, the patients were asked to eat or drink nothing for 6 h. Antacids and H2 receptor antagonists were discontinued 24 h before the test. One week prior to the test, proton pump inhibitors and sucralfate were stopped (17). Antibiotics were discontinued over a month before the test.…”
Section: C14 Ubtmentioning
confidence: 99%
“…Gastric ulceration and carcinogenesis are associated with HP infection (11). HP infection has been linked to various autoimmune dermatological diseases, such as alopecia areata, Behçet's disease, chronic urticaria, pruritus, psoriasis, and rosacea (12)(13)(14)(15)(16)(17). The frequency of HP has not been studied in patients with vitiligo.…”
Section: Introductionmentioning
confidence: 99%